The Effectiveness of Facet Joint Local Corticosteroid Injection in Diagnosis and Treatment of Facet Joint Syndrome - Amr Sabry AlBakry; Ahmed Saleh ElSayed; Hamada Mostafa AbdulAal; ElSaid Hamdy Zaki (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objectives: To evaluate outcomes of lumbar facet joint injection with local corticosteroid in treatmentof chronic low back pain according to Oswestry disability Index(ODI).Patients and Methods: Interventional prospective study on 23 patients attended the outpatient clinic ofOrthopedic Surgery in Cairo University Hospitalscomplaining of chronic low back pain not responsiveto medical treatment and physiotherapy from September 2018 to august 2019.Results: The mean age of the patients was 41.17 ± 9.74 years and 47.8% were males. Facet jointcorticosteroid injection resulted in significant reduction of pain severity of patients as it ranged 5:10(mean 7.3 ±1.5) pre-injection and improved to 0 :6 (mean 3.6 ± 1.7) 3-month post injection(Pvalue:0.001)while the ODI score ranged 26:80 (mean 47.4 ±15.7) pre-injection and improved to 4:46 (mean 28.8 ±10.4) three months post injection(Pvalue 0.001).Conclusion: intra-articular facet joint injection is crucial in the diagnosis and treatment of facet jointsyndrome.